Incidence and risk factors for musculoskeletal adverse effects associated with daptomycin in patients receiving outpatient parenteral antimicrobial therapy - Meaghen B. Wiley; Kiya K. Bennett; Emily A. Siegrist; Stephen B. Neely; Joseph Sassine; Bryan P. White (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Abstract